12-3×11×[10-7×(13-2×6)=
Răspunsuri la întrebare
Răspuns de
0
12-3x11x[10-7x(13-2x6)]=
12-3x11x[10-7x(13-12)]=
12-3x11x(10-7x1)=
12-3×11×(10-7)=
11-3×11×3=
11-33×3=
11-99= - 88
Răspuns de
0
12 - 3 × 11 × [ 10 - 7 × ( 13 - 2 × 6 ) ] =
12 - 33 × [ 10 - 7 × ( 13 - 12 ) ] =
12 - 33 × ( 10 - 7 × 1 ) =
12 - 33 × ( 10 - 7 ) =
12 - 33 × 3 =
12 - 99 = - 87
12 - 33 × [ 10 - 7 × ( 13 - 12 ) ] =
12 - 33 × ( 10 - 7 × 1 ) =
12 - 33 × ( 10 - 7 ) =
12 - 33 × 3 =
12 - 99 = - 87
Alte întrebări interesante
Limba română,
8 ani în urmă
Biologie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă